PENGARUH ECONOMIC VALUE ADDED, RESIDUAL INCOME, EARNINGS, OPERATING CASH FLOW DAN OPERATING LEVERAGE TERHADAP RETURN SAHAM PADA PERUSAHAAN LQ 45 - Rima Fathonah Oktaviani; Hotman T. Pohan (Jurnal Magister Akuntansi Trisakti, 2017)
The purpose of this study was to determine the influence between economic value added, residual income, eranings, operating cash flow and operating leverage on stock returns.The population of this study is company LQ 45. The sample of the study was obtained by purposive sampling method where are 26 same companies each year and meet the sampling criteria. The study period is 2012 to 2015.This study found that there is a positive influence between  economic value added, residual income, operating cash flow, and operating leverage on stock returns on company LQ 45. But for earnings there is not effect on stock return on company LQ 45.